2020
DOI: 10.1017/s0031182020000116
|View full text |Cite
|
Sign up to set email alerts
|

Complete sporogony of the blood parasite Haemoproteus nucleocondensus in common biting midges: why is its transmission interrupted in Europe?

Abstract: Haemoproteus species (Haemoproteidae) are widespread blood parasites and are transmitted by Culicoides biting midges and Hippoboscidae louse flies. Although these pathogens may cause morbidity or mortality, the vectors and patterns of transmission remain unknown for the great majority of avian haemoproteids. Haemoproteus nucleocondensus has been frequently reported in Europe in great reed warblers Acrocephalus arundinaceus after their arrival from African wintering grounds, but this infection has not been foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(106 reference statements)
0
2
1
Order By: Relevance
“…However, June might be the month when biting midges have their first blood meal and are free of parasites. For instance, there are no records of H. nucleocondensus local transmission, a parasite of great reed warbler (Acrocephalus arundinaceus) in juvenile birds in northern Europe, although locally abundant Culicoides species could serve as vector candidates for H. nucleocondensus transmission [38,39]. The maximum hatching and fledging period of great read warblers occurs in June and vector abundance, according to our investigations, is high at that time [39].…”
Section: Discussioncontrasting
confidence: 47%
“…However, June might be the month when biting midges have their first blood meal and are free of parasites. For instance, there are no records of H. nucleocondensus local transmission, a parasite of great reed warbler (Acrocephalus arundinaceus) in juvenile birds in northern Europe, although locally abundant Culicoides species could serve as vector candidates for H. nucleocondensus transmission [38,39]. The maximum hatching and fledging period of great read warblers occurs in June and vector abundance, according to our investigations, is high at that time [39].…”
Section: Discussioncontrasting
confidence: 47%
“…In birds, louse flies are responsible for the transmission of parasites such as Haemoproteus spp. involved in bird mortality and morbidity [30]. Until this study, the only louse flies identified in Corsica were collected on bats and belonged to the family Nycteribiidae.…”
Section: Introductionmentioning
confidence: 97%
“…Some of these Plasmodium parasites are highly virulent to European bird species [23][24][25][26]. The tropical haemosporidians are not transmitted in the temperate zone of Europe, although, the possibility to complete their development in local vectors (i.e., sporogonic development) or avian hosts has been demonstrated [24,[26][27][28][29]. Plasmodium relictum (pGRW4) infects more than 80 bird species and has transmission mostly in tropical regions and the Americas [30].…”
Section: Introductionmentioning
confidence: 99%